2021
DOI: 10.1155/2021/4391864
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Automatic Parking System Based on Improved Neural Network Algorithm and Intelligent Image Analysis

Abstract: This research designs an intelligent parking system including service application layer, perception layer, data analysis layer, and management layer. The network system adopts opm15 system, and the parking space recognition adopts improved convolution neural networks (CNNs) algorithm and image recognition technology. Firstly, the parking space is occupied and located, and the shortest path (Dynamic Programming, DP) is selected. In order to describe the path algorithm, the parking system model is established. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For this purpose, a convolutional neural network is an advanced form of a regular artificial neural network. The main difference between them is related to both convolutional and pooling layers in CNN models [4]. Therefore, the values in the hidden layers in the CNN are considered linear transformation of the previous parameters with ANN.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a convolutional neural network is an advanced form of a regular artificial neural network. The main difference between them is related to both convolutional and pooling layers in CNN models [4]. Therefore, the values in the hidden layers in the CNN are considered linear transformation of the previous parameters with ANN.…”
Section: Related Workmentioning
confidence: 99%
“…Some of them are allowing smooth traffic flow on the roads and also increasing the efficiency of the parking system. The main concept of the parking system is executed by using various approaches [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%